2018
DOI: 10.1080/10810730.2018.1511658
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Use and Trust in Health Information

Abstract: There is a need to investigate which health information sources are used and trusted by people with limited health literacy to help identify strategies for addressing knowledge gaps that can contribute to preventable illness. We examined whether health literacy was associated with people's use of and trust in a range of potential health information sources. Six hundred participants from a GfK Internet survey panel completed an online survey. We assessed health literacy using the Newest Vital Sign, the sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
268
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(291 citation statements)
references
References 76 publications
17
268
1
5
Order By: Relevance
“…Telemedicine, which uses interactive audio‐visual tools so the usual face‐to‐face communication between physician and patient is not required, could be used to improve access to and use of health information from health professionals in rural areas . Health professionals could develop interventions that target rural residents with limited health literacy to enhance their ability to evaluate the quality of health information, especially information from for‐profit companies . In newspapers and magazines, rural residents would also benefit from tailored health news, eliminating medical terms, and adding figures and pictures to help them understand the health information .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Telemedicine, which uses interactive audio‐visual tools so the usual face‐to‐face communication between physician and patient is not required, could be used to improve access to and use of health information from health professionals in rural areas . Health professionals could develop interventions that target rural residents with limited health literacy to enhance their ability to evaluate the quality of health information, especially information from for‐profit companies . In newspapers and magazines, rural residents would also benefit from tailored health news, eliminating medical terms, and adding figures and pictures to help them understand the health information .…”
Section: Discussionmentioning
confidence: 99%
“…58,59 Health professionals could develop interventions that target rural residents with limited health literacy to enhance their ability to evaluate the quality of health information, especially information from for-profit companies. 24 In newspapers and magazines, rural residents would also benefit from tailored health news, eliminating medical terms, and adding figures and pictures to help them understand the health information. 60,61 In addition, a lack of statistical significance does not necessarily mean a lack of clinical or practical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In turn, prior studies have shown that lower health literacy is linked to lower levels of trust in physicians. 22,23 The subgroup analysis of insurance status showed expected and unexpected ndings. Prior studies show that patients with Medicare or Medicaid have lower health literacy than patients with private insurance.…”
Section: Discussionmentioning
confidence: 96%
“…In order for the doctor, dental surgeon and other health professionals to diagnose a cancer, in addition to understanding the subject, they must admit the possibility of this disease 1 . Measuring the knowledge of these professionals contributes to the strengthening of policies to combat cancer [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%